2017
DOI: 10.1016/j.bbrc.2016.11.050
|View full text |Cite
|
Sign up to set email alerts
|

AICAR activates ER stress-dependent apoptosis in gallbladder cancer cells

Abstract: AICAR (5-Aminoimidazole-4-carboxamide riboside or acadesine) is an AMP-activated protein kinase (AMPK) agonist, its activity in human gallbladder cancer cells was evaluated here. We show that AICAR provoked significant apoptosis in human gallbladder cancer cell lines (Mz-ChA-1, QBC939 and GBC-SD) and primary gallbladder cancer cells. AICAR-induced cytotoxicity in gallbladder cancer cells appears independent of AMPK activation. Inhibition of AMPK, via AMPKα shRNA knockdown or dominant negative mutation (T172A),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…For instance, it is able to induce programmed necrosis in prostate cancer cells through a cytotoxic mechanism involving reactive oxygen species 18 . AICAR/ZMP is also capable of inducing cellular apoptosis in human osteosarcoma cells, 19 or in gallbladder cancer cells through a cytotoxic mechanism involving endoplasmic reticulum‐stress activation 20 . AICA‐riboside has also demonstrated pro‐apoptotic abilities in a cellular model of von Hippel‐Lindau renal carcinoma and been able to reduce the size of renal tumors in a mouse model 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it is able to induce programmed necrosis in prostate cancer cells through a cytotoxic mechanism involving reactive oxygen species 18 . AICAR/ZMP is also capable of inducing cellular apoptosis in human osteosarcoma cells, 19 or in gallbladder cancer cells through a cytotoxic mechanism involving endoplasmic reticulum‐stress activation 20 . AICA‐riboside has also demonstrated pro‐apoptotic abilities in a cellular model of von Hippel‐Lindau renal carcinoma and been able to reduce the size of renal tumors in a mouse model 21 .…”
Section: Discussionmentioning
confidence: 99%
“…18 AICAR/ ZMP is also capable of inducing cellular apoptosis in human osteosarcoma cells, 19 or in gallbladder cancer cells through a cytotoxic mechanism involving endoplasmic reticulum-stress activation. 20 AICA-riboside has also demonstrated pro-apoptotic abilities in a cellular model of von Hippel-Lindau renal carcinoma and been able to reduce the size of renal tumors in a mouse model. 21 Its AMPK-independent anti-tumoral properties could result from the activation of the tumor suppressor genes LATS1 and LATS2.…”
Section: Pathological Mechanism Of Aica-ribosiduriamentioning
confidence: 99%
“…Normal human gallbladder epithelial cells were not necessarily used as control cells in most articles [10][11][12][13][14]. The primary cells of human gallbladder epithelium were isolated and used as the research objects in a few articles according to their research needs [15]. Since the purpose of this study is to evaluate the effect of Bufalin on gallbladder cancer cells, the results of this study mainly reflect the changes of biological characteristics of human gallbladder cancer epithelial cells before and after treatment.…”
Section: Bufalin Suppressed Xenografted Gallbladder Cancer Growth In mentioning
confidence: 99%
“…In addition, a study by Yung et al ( 77 ) demonstrated increased Ser 473 phosphorylation alongside decreased Thr 308 AKT residues that were modulated by ER stress in choriocarcinoma cells. In addition, previous descriptions of the ER stress response in tumor cells related to treatments with adenosine ( 78 ) and its analogue AICAR ( 79 ) further supports the notion.…”
Section: Discussionmentioning
confidence: 55%